Komposisi Dan Kelimpahan Fitoplankton Di Perairan Pasuruan - Putri Anugerah; Noorsheha Noorsheha; Ricko Reynalta (KOLONI, 2023)
Pasuruan sea waters are one of the strategic waters in East Java Province. Ecologically, Pasuruan Waters is a habitat for various types of aquatic organisms including phytoplankton. The Pasuruan sea area is the estuary of the rivers in Pasuruan which carry household, factory and other waste. This is feared to result in a decrease in water quality which can interfere with the growth of phytoplankton in the waters. Phytoplankton is a biological parameter that can be used as a bioindicator to evaluate the quality and fertility of a waters. The purpose of this study was to determine the composition and abundance of phytoplankton in Pasuruan Waters, East Java. This study used a descriptive explorative method with data collection using a purposive sampling method. The results showed that 22 genera were found from 5 divisions, namely the Chlorophyta division (6 genera), the Baccilariophyta division (11 genera), the Miozoa division (1 genera), the Cyanobacteria division (3 genera), and the Dinoflagellate division (1 genera). The abundance of phytoplankton ranges from 961 – 1815 cells/liter. The diversity index is in the low category with a range between 0 – 0.153. The dominance index of 0.6 - 0.8 indicates dominance in the waters and shows that the community structure is unstable. The dominant type of phytoplankton is Bacillariophyta.  Keywords:  Composition, abundance, phytoplankton, Pasuruan waters